KETAHANAN RUMAH TANGGA PELAKU HOMOSEKSUAL DAN LESBIAN - Rafika Ridhaizzati; Nurus Shalihin (Turast: Jurnal Penelitian dan Pengabdian, 2022)
This study aims to explore why homosexual and lesbian households can survive as couples' households in general. The research method in this study is a qualitative research with a case study approach. The data in this study were collected using in-depth interview techniques. The data sources in this study are primary data sources taken from homosexual and lesbian families. This study found that there are two factors that cause homosexual and lesbian families to survive. First, the presence of children in a homosexual family becomes a mediation that can reduce both partners, even though the husband or wife already knows that homosexuality and lesbianism are deviant acts. Second, economic dependence, such as doubts about the establishment of life, is also a factor in the survival of homosexual and lesbian households. This study concludes that although homosexuals and lesbians are deviant behaviors, there are conditions and factors that cause homo and lesbi families to persist.